From the Augustan Principate to the Invention of the Age of Augustus. (November 2019) - Cooley, Alison E.
ABSTRACT: This paper explores alternatives to analysing the political impact of Augustus in terms of the establishment of a new constitutional structure, the Augustan Principate. It starts by showing how the word principatus changed over time and explores the significance of the term statio . It considers how contemporaries viewed the political changes that occurred during Augustus' lifetime, analysing the ways in which power at Rome became increasingly embodied in the person of Augustus himself. It suggests that there was an increasing recognition that Augustus was an exceptional individual, whose position in the state was supported by powers granted formally by senatorial decree and popular vote as well as informally by acclamation, but whose authority was ultimately a personal quality, supported by the gods, and predestined by birth. It traces the ways in which Augustus' rule became increasingly personalised, with the result that one of the main challenges faced by Tiberius in a.d . 14 was how to take over Augustus' personal role as princeps .